2019
DOI: 10.5964/jspp.v7i1.746
|View full text |Cite
|
Sign up to set email alerts
|

Agentic and communal interaction goals in conflictual intergroup relations

Abstract: Members of conflicting groups experience threats to different identity dimensions, resulting in the need to restore the aspect of identity that was threatened. Do these needs translate into specific goals in social interactions? In the present research, we examined the hypotheses that (1) experiencing one’s ingroup as illegitimately disadvantaged or victimized arouses agentic goals (to act and appear assertive and confident) when interacting with the advantaged or victimizing group, while (2) experiencing one’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 42 publications
2
16
0
Order By: Relevance
“…The NBMR claims that both parties' need satisfaction is possible by engaging in a bilateral strategy in which perpetrators empower victims by apologizing and asking for their forgiveness while victims try to empathize and accept the perpetrators as fellow human beings. The model's basic tenets have been supported in a number of empirical studies in the context of interpersonal transgressions (e.g., Shnabel & Nadler, 2008) and of intergroup transgressions (e.g., Aydin, Ullrich, Siem, Locke, & Shnabel, 2019;Shnabel, Nadler, Ullrich, Dovidio, & Carmi, 2009; see also Siem, von Oettingen, Mummendey, & Nadler, 2013). Results from these studies convergingly confirmed the differing needs structure in victims (or members of victimized groups) and perpetrators (or members of perpetrating groups) and how messages of acceptance and empowerment are facilitating reconciliation if they fit the needs of the recipient (group) (for an overview, see Shnabel & Nadler, 2015).…”
Section: Theoretical Framework: the Needs-based Model Of Reconciliationmentioning
confidence: 93%
“…The NBMR claims that both parties' need satisfaction is possible by engaging in a bilateral strategy in which perpetrators empower victims by apologizing and asking for their forgiveness while victims try to empathize and accept the perpetrators as fellow human beings. The model's basic tenets have been supported in a number of empirical studies in the context of interpersonal transgressions (e.g., Shnabel & Nadler, 2008) and of intergroup transgressions (e.g., Aydin, Ullrich, Siem, Locke, & Shnabel, 2019;Shnabel, Nadler, Ullrich, Dovidio, & Carmi, 2009; see also Siem, von Oettingen, Mummendey, & Nadler, 2013). Results from these studies convergingly confirmed the differing needs structure in victims (or members of victimized groups) and perpetrators (or members of perpetrating groups) and how messages of acceptance and empowerment are facilitating reconciliation if they fit the needs of the recipient (group) (for an overview, see Shnabel & Nadler, 2015).…”
Section: Theoretical Framework: the Needs-based Model Of Reconciliationmentioning
confidence: 93%
“…"; see also Inman, 2001). Further, members of advantaged groups generally avoid discussions about group differences in power and prefer to talk about what they have in common instead (Aydin et al, 2019;Bergsieker et al, 2010;Saguy & Dovidio, 2013;Saguy & Kteily, 2014).…”
Section: Implications Of Contact Interventions Aiming To Foster Sociamentioning
confidence: 99%
“…Whereas earlier research examined the needs-based model in contexts of direct violence, in which the roles of "victim" and "perpetrator" groups is consensual and clear-cut (e.g., the Holocaust; Shnabel et al, 2009), subsequent research examined it in contexts of so-called 'structural violence' (i.e., groupbased inequality, Galtung, 1969), which is characterized by ambiguity with regard to the advantaged group's "culpability." Aydin A. L. et al (2019) revealed that the psychological needs of advantaged and disadvantaged group members (e.g., members of higher and lower social classes; correspond to those of victims and perpetrators. Whereas disadvantaged group members experience threat to their status and identity as competent and are therefore motivated to gain respect (Bergsieker et al, 2010), advantaged group members experience threat to their moral identity (e.g., they may be perceived as prejudiced and bigoted, Fiske et al, 2002) and therefore seek moral-social acceptance (Bergsieker et al, 2010).…”
Section: Group Members' Needs For Empowerment and Morality: The Perspmentioning
confidence: 99%